Laparoscopic repair for neonatal spontaneous gastric perforation: a case report - Wu, Jianqing; Ye, Lin; Wang, Xiqin; Zhang, Heng (Frontiers in Surgery, 2025)
BackgroundSpontaneous neonatal gastric perforation (SNGP) is an extremely rare but life-threatening surgical emergency. Open surgery has been the traditional mainstay of treatment, whereas reports on laparoscopic repair in neonates remain scarce. This report delineates a successful case of laparoscopic repair for SNGP in a newborn. We herein detail the surgical technique and elucidate the advantages of this minimally invasive approach over conventional open surgery.Case presentationA 34-week premature male neonate, with a birth weight of 2550 grams and born to a G6P4 mother, was admitted presenting with a one-day history of vomiting and abdominal distension. An abdominal x-ray obtained at a referring hospital demonstrated pneumoperitoneum, suggestive of neonatal gastrointestinal perforation. Upon transfer to our institution, a repeat abdominal x-ray revealed massive subdiaphragmatic free air, elevated diaphragmatic arches, and central clustering of bowel loops, constituting the classic “football sign.” A preliminary diagnosis of spontaneous neonatal gastric perforation was established. The patient subsequently underwent emergent laparoscopic repair of the gastric perforation. Postoperatively, he was transferred to the neonatal intensive care unit (NICU) for close monitoring. Full enteral feeding was gradually reestablished, commencing on the seventh postoperative day.ConclusionIn this case, a newborn with SNGP was successfully managed via laparoscopic repair. This case underscores the potential of minimally invasive techniques for managing this condition. The laparoscopic approach provided superior visualization of the gastric fundus and facilitated enhanced vessel mobilization compared to open surgery. The patient's uneventful postoperative recovery exemplifies the documented advantages of laparoscopy, including reduced tissue trauma, diminished postoperative pain, and a more rapid recovery. We therefore conclude that, for hemodynamically stable neonates in centers with appropriate surgical expertise, laparoscopic repair represents a viable and advantageous alternative to open surgery.